Exploratory Longitudinal Cohort Study of Associations of Fatigue After Stroke. Issue 4 (April 2015) - Duncan, Fiona; Lewis, Susan J.; Greig, Carolyn A.; Dennis, Martin S.; Sharpe, Michael; MacLullich, Alasdair M.J.; Mead, Gillian E.
<x xml:space="preserve">Abstract</x> Background and Purpose— The pathogenesis of poststroke fatigue is unclear. In this prospective study, we explored whether reduced physical activity might contribute to poststroke fatigue or be a consequence of it. Methods— Patients with a recent acute stroke were assessed at 1, 6, and 12 months with, Fatigue Assessment Scale (FAS), a fatigue case definition, Hospital Anxiety and Depression Score, sleepiness, quality of life, and accelerometry (ActivPAL). Bivariate analyses determined associations between fatigue and step count at each time point. Multiple linear regression tested whether 1-month step count independently predicted 6- and 12-month FAS. Results— A total of 136 participants (mean age, 72 years; 64% men) attended ≥1 assessment. ActivPAL data were available for 84 (64%), 69 (66%), and 58 (64%) participants at 1, 6, and 12 months, respectively. At 6 and 12 months, a positive fatigue case definition was associated with lower daily step counts (P=0.014 and 0.013, respectively). At 1, 6, and 12 months, higher FAS (more fatigue) was associated with lower step count (P<0.001, 0.01, and 0.007), higher depression (P<0.001), anxiety scores (P<0.001) and sleepiness (P<0.001), and poorer quality of life (P<0.001). Lower daily step count (P<0.002 and 0.006) and greater anxiety (P<0.001 for both) at 1 month independently predicted higher FAS at 6 and 12 months. Conclusions— Lower step counts at 1 month independently predicted greater FAS for ⩽12 months. Physical activity might be a therapeutic target for poststroke fatigue.